Social engineering based security requirements elicitation model for advanced persistent threats - Kim, Seung Jun; Lee, Seok Won (Communications in Computer and Information Science, 2018)
APT attacks are increasing every year, and these APT attacks begin with social engineering attacks. In order to be effective in blocking APT attacks, blocking social engineering attacks make it possible to prevent APT attacks in advance. In this study, we define human factors which greatly influence social engineering attacks, and make it possible to obtain appropriate security requirements by modeling the relationships among human vulnerability, social engineering attacks and security requirements.
Keywords: Advanced persistent threat; Security requirements; Social engineering; Advanced persistent threat; Human factor; Ontology; Security requirement; Social engineering attack